Pengaruh Perputaran Kas, Perputaran Piutang Terhadap Profitabilitas dengan Likuiditas Sebagai Variabel Intervening: Studi Kasus Pada Bank Perkreditan Rakyat (BPR) Kabupaten Tangerang 2016-2020 - Hanifatul Riskiya; Mayang Sari Edastami (JUDICIOUS, 2023)
This study aims to examine and analyze the effect of cash turnover, accounts receivable turnover, on profitability with liquidity as an intervening variable. The sample of this research is Rural Banks (BPR) of Tangerang Regency which are registered with the Financial Services Authority (OJK) for the period 2016 to 2020. The data analysis technique uses multiple linear regression and path analysis. The results showed that simultaneously cash turnover, receivables turnover with liquidity as an intervening variable affected profitability. Partially, cash turnover and liquidity variables have a significant positive effect on liquidity, but receivables turnover does not have a significant positive effect on liquidity. Then partially cash turnover and receivables have a significant positive effect on profitability. Hypothesis testing using path analysis test that the current liquidity ratio (CR) functions as an intervening variable cannot mediate between the independent variables cash turnover and receivables turnover on profitability (ROA).